Towards Participatory Worldview in Education and Research: A Philosophical Inquiry on the Question- Why Participatory? - Wagle, Shree Krishna (Journal of Transformative Praxis, 2022)
This article portrays the author’s philosophical inquiry on the prospects of a participatory worldview in education and research. To this, the author begins his inquiry process, reflecting upon his own personal/ professional shift from rational (analytical) academician to the transformative educational practitioner. The reflection further depicts his continuous inclination towards participatory science and worldviews. The author reflects upon his personal/ professional journey, which seemingly is parallel to the spiral of human civilization from participatory to (post)positivist to constructivist to transformative to participatory again. From there, the author makes philosophical observation at genealogical progression (spiral) of participatory worldview both in the East and the West. Also, the author observes current developments in the field of quantum science and renders how such developments have paved manifold ways for a participatory worldview in Social Science, particularly in education and research.